2020
DOI: 10.7903/cmr.20334
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Role of Job Satisfaction on Internal Corporate Social Responsibility Practices and Employee Engagement in Higher Education Sector

Abstract: The study aims to investigate the relationship between internal corporate social responsibility (ICSR) practices and employee engagement through job satisfaction as a mediating variable. The ICSR dimensions are comprised of employee empowerment, education and training, employment stability, as well as a working environment. This study is based on the social exchange theory to explore the relationship between the above factors and ICSR. In this study, purposive sampling was adopted. A quantitative (survey) meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
3
19
0
Order By: Relevance
“…Before testing the model, we first tested whether there was bias in the data collection. Whether there is bias in data collection, the common method variance (CMV) test (Hossen, Chan, & Hasan, 2020). In this study, the CMV test used the correlation matrix procedure (Tehseen, Ramayah, & Sajilan, 2017).…”
Section: Results and Discussion 1 Demographics Of Respondentmentioning
confidence: 99%
See 1 more Smart Citation
“…Before testing the model, we first tested whether there was bias in the data collection. Whether there is bias in data collection, the common method variance (CMV) test (Hossen, Chan, & Hasan, 2020). In this study, the CMV test used the correlation matrix procedure (Tehseen, Ramayah, & Sajilan, 2017).…”
Section: Results and Discussion 1 Demographics Of Respondentmentioning
confidence: 99%
“…The bootstrapping method can be used to analyze the indirect effects of the bootstrapping method (Hossen et al, 2020). The results of testing the mediating effects of the attitude variables are presented in Table 8.…”
Section: Moderating Analysismentioning
confidence: 99%
“…The recent PLS-SEM guidelines include nonlinear effects, endogeneity, and unobserved heterogeneity as compulsory for any analysis (Latan, 2018). PLS-SEM is a popular methodology in recent studies relevant to consumer/users' behavior (Blasco Lopez et al, 2018;Chiang et al, 2019;Hossen et al, 2020;Marmaya et al, 2019). Therefore, this study adopted PLS-SEM to examine the influential factors on impulse buying behavior.…”
Section: Methodology Pls-sem (Partial Least Square Structural Equation Model)mentioning
confidence: 99%
“…ExCSR involves stakeholders outside the organization and has been extensively studied in the literature, but there are few studies from the internal aspect perspective on an employee's perception of benefit related to CSR activities [50]. The trend of InCSR research is increasing in the field of organization [51], and studies involving InCSR are important due to the fact that it often helps attract and retain employees [52]. Previous studies confirmed that CSR policies play a role in motivating employees [53]; however, we focus on the aspect of InCSR for the purpose of our research.…”
Section: Employee Perceptions Of Incsrmentioning
confidence: 99%